Discovery, characterization, and clinical development of the glucagon-like peptides - Drucker, Daniel J. (J Clin Invest, 2017)
The discovery, characterization, and clinical development of glucagon-like-peptide-1 (GLP-1) spans more than 30 years and includes contributions from multiple investigators, science recognized by the 2017 Harrington Award Prize for Innovation in Medicine. Herein, we provide perspectives on the historical events and key experimental findings establishing the biology of GLP-1 as an insulin-stimulating glucoregulatory hormone. Important attributes of GLP-1 action and enteroendocrine science are reviewed, with emphasis on mechanistic advances and clinical proof-of-concept studies. The discovery that GLP-2 promotes mucosal growth in the intestine is described, and key findings from both preclinical studies and the GLP-2 clinical development program for short bowel syndrome (SBS) are reviewed. Finally, we summarize recent progress in GLP biology, highlighting emerging concepts and scientific insights with translational relevance.